Survey for Natural Incidence of Diseases in Rabi Soybean in Telangana, India - , Bhargavi Putta; , Balram Nenavath; , S. Ameer Basha; , S. N. C. V. L Pushpavalli (Archives of Current Research International, 2025)
Soybean (Glycine max (L.) Merrill) also known as “Miracle Crop”, is a major oil seed crop grown worldwide. The present study was undertaken to assess the incidence of soybean diseases during rabi 2023-24. Roving surveys were conducted in Adilabad, Jagtial, Nizamabad, Kamareddy districts of Telangana state. The survey results revealed that, the highest incidence of Alternaria disease (40.30%) was recorded in Nizamabad, while the lowest (8.60%) in Adilabad. Yellow Mosaic Disease had the highest incidence (52.4%) in Jagtial and the lowest (11.2%) in Adilabad. Jagtial also recorded the highest incidence of both, dry root rot (42.9%) and anthracnose (16.8%), whereas Kamareddy reported no incidence (0%) of these diseases at the vegetative stage. Nizamabad had the highest incidence of both powdery mildew (12.4%) and sudden death syndrome (6.4%). These findings highlight the need for awareness and the implementation of effective management strategies to control soybean diseases in the affected districts.